VILLAGE GOVERNMENTS EFFORTS IN INCREASING THE WORK DISCIPLINE OF VILLAGE APPARATUS IN GERA VILLAGE SIKKA DISTRICT - Maria Vevilia Nestin; Danar Aswim (Institut Pendidikan Indonesia, 2023)
This research as conducted to find out the illage Goernments Efforts to Improe the ork Discipline of illage fficials in Gera illage Mego District Sikka egenc and hat factors hindered the illage Goernments efforts to improe the ork discipline of illage fficials. This research method as carried out using a ualitatie descriptie approach. The data sources used ere primar data sources and secondar data sources. The informants seen in this stud ere the illage ead illage fficials and illage ommunities. Data collection techniues used are oseration techniues interies and documentation. Data analsis techniues include data reduction data reduction data displa data presentation and conclusion draingerification. The results of the stud shoed that the illage Goernments efforts to improe the ork discipline of illage officials in Gera illage Mego District Sikka egenc ere carried out means of Special Guidance for pparatuses and there ere seeral inhiiting factors in increasing the ork discipline of illage pparatuses namel the topograph factor or er difficult road terrain man officials did not ons a priate ehicle and the illage ead and illage fficials lie far from the illage ffice. This stud suggests that to improe the ork discipline of illage officials it is est if the illage ead proides continuous motiation aout the importance of discipline at ork. The illage head should immediatel make illage regulations as a asis for improing the ork discipline of illage officials including giing aards and sanctions to illage officials. s ell as the illage ead must pa attention to the attendance list eer time he enters orking hours and comes home from ork as a tool for controlling.